Profile of Students' Critical Thinking Skills and the Implementation of PBLRQA based on Blended Learning in Senior High School - Febtya Lailatul Badriyah; Husni Mubarok; Binar Kurnia Prahani (IKIP Mataram, 2021)
This research aimed to obtain the profile of students' critical thinking skills and the implementation of PBLRQA based on blended learning in high school. This research is a descriptive preliminary study with a saturated sampling technique was taken by 123 students. The method of gathering information with a used a written test, response questionnaire students, and teacher interviews. The analysis was conducted using qualitative descriptive analysis techniques. The result showed that critical thinking skills in the very low category. With the acquisitions of the very low category as many as namely 110 students, the low category as many as 12 students being low, the medium category as many as and 1 student, but in the high and very high categories there are no students who achieve it. The research of the study concluded that the students generally in low critical thinking skills, so it is necessary to change the learning model to improve critical thinking skills, namely by the implementation of PBLRQA based on blended learning.